Individual sprint force-velocity profile adaptations to in-season assisted and resisted velocity-based training in professional rugby - Lahti, J.; Jiménez-Reyes, P.; Cross, M. R.; Samozino, P.; Chassaing, P.; Simond-Cote, B.; Ahtiainen, J. P.; Morin, J.-B. (Sports, 2020)
We tested the hypothesis that the degree of adaptation to highly focused sprint training at opposite ends of the sprint Force-Velocity (FV) spectrum would be associated with initial sprint FV profile in rugby athletes. Training-induced changes in sprint FV profiles were computed before and after an eight-week in-season resisted or assisted sprint training protocol, including a three-week taper. Professional male rugby players (age: 18.9 ± 1.0 years; body height: 1.9 ± 0.0 m; body mass: 88.3 ± 10.0 kg) were divided into two groups based on their initial sprint FV profiles: 1) Heavy sled training (RESISTED, N = 9, velocity loss 70-80%), and 2) assisted acceleration training (ASSISTED, N = 12, velocity increase 5-10%). A total of 16 athletes were able to finish all required measurements and sessions. According to the hypothesis, a significant correlation was found between initial sprint FV profile and relative change in sprint FV profile (RESISTED: r = -0.95, p < 0.01, ASSISTED: r = -0.79, p < 0.01). This study showed that initial FV properties influence the degree of mechanical response when training at different ends of the FV spectrum. Practitioners should consider utilizing the sprint FV profile to improve the individual effectiveness of resisted and assisted sprint training programs in high-level rugby athletes.